Pelayanan Kargo Udara di Terminal Kargo Domestik Bandar Udara Soekarno-Hatta - Sitti Subekti (Research and Development Agency of The Ministry of Transportation, 2013)
The compliance of users expectations on services air cargo is an important thing for organizations to face the competition of business services. Air cargo services in this study were measured with the dimensions of SERVQUAL model. Dimensions of quality that is used consist of the dimensions of reliability, responsiveness, assurance, empathy and tangible which covers 15 attributes of service. Service attribute is used to assess the quality of service warehouse operator PT Garuda Indonesia and PT Gapura Angkasa on domestic cargo terminal Soekarno-Hatta Airport. The research sample consisted of 46 service quality in the warehouse operator PT Garuda Indonesia Cargo and 33 in PT Gapura Angkasa. Service attributes were analyzed by Importance Performance Analysis. The most importances of services attributes consist of on-time delivery capabilities, delivering a record / document without errors, communication with customers and time coordination, the service immediately / quickly for customers, compensation for damages or missing items and the clarity and completeness of the operational procedures. Increased air cargo services and customer satisfaction index in the domestic cargo terminal can be done with corrective measures on the attributes of service that is located in quadrant one. Pemenuhan harapan pengguna kargo terhadap pelayanan kargo udara merupakan hal penting bagi organisasi jasa untuk menghadapi persaingan bisnis. Pelayanan kargo udara dalam penelitian ini diukur dengan dimensi model Servqual. Dimensi kualitas yang digunakan terdiri dari dimensi reliabilitas, daya tanggap, jaminan, empati dan bukti fisik yang meliputi 15 atribut jasa.Atribut jasa tersebut digunakan untuk menilai kualitas pelayanan warehouse operator PT Garuda Indonesia Cargo dan PT Gapura Angkasa pada terminal kargo Domestik Bandar Udara Soekarno-Hatta.Sampel penelitian kualitas pelayanan terdiri dari 46 pada warehouse operator PT Garuda Indonesia Cargo dan 33 pada PT Gapura Angkasa.Atribut jasa dianalisis dengan Importance Performance Analysis.Atribut jasa penting terdiri dari kemampuan pengiriman tepat waktu, menyampaikan catatan/dokumen tanpa kesalahan, komunikasi dengan pelanggan dan mengkoordnasi waktu, layanan yang segera/cepat bagi pelanggan, kompensasi untuk kerusakan atau barang hilang dan kejelasan dan kelengkapan prosedur operasional.Peningkatan pelayanan kargo udara dan indeks kepuasan pengguna di terminal kargo domestik dapat dilakukan dengan langkah perbaikan pada atribut jasa yang terletak pada kuadran satu.